The front sqaut and its variations - Waller, M.; Townsend, R. (Strength and Conditioning Journal, 2007)
This article discusses the technical aspects of the front squat along with its variations that may be utilized by a strength and conditioning professional to increase lower extremity strength. It is the goal of the article to provide a basis on why to use the front squat or its variations in a strength program, which will hopefully lead to further research involving the front squat.